EFFECT OF TELENURSING ON THE ADAPTIVE PROCESS OF PEOPLE WITH INTESTINAL STOMA: CLINICAL TRIAL (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To analyze the effect of telenursing on the adaptive process of people with intestinal ostomy. Method: Randomized, single-blind clinical trial. The verification scale of the level of adaptation of the person with ostomy was applied, and two groups were formed. The control group received conventional care with professionals from the reference center, and the intervention group received conventional follow-up associated with the complementary intervention via telephone (three phone calls on the 20th, 40th and 60th day after initial contact). At the end of the intervention, the participants were evaluated again through the scale. Recruitment occurred from the first contact and had a sample of 16 participants in the intervention group and 17 in the control group. Results: There was a similarity in the levels of adaptation at baseline between the two groups. However, post-intervention data showed a significant difference between the groups during the study and lower values of the means of the control group compared to the measures of the intervention group, demonstrating a higher level of adaptation in the intervention group. Conclusion: The study verified the effect of telenursing on the adaptive process of the person with a stoma and suggests benefits in complementary monitoring via telenursing at the level of adaptation of people with a stoma after ≤ 12 months of surgery.